A prospective cohort study of load and wellness (sleep, fatigue, soreness, stress, and mood) in elite junior Australian football players - Lathlean, T. J. H.; Gastin, P. B.; Newstead, S. V.; Finch, C. F. (International Journal of Sports Physiology and Performance, 2019)
In order to transition successfully to the Australian Football League (AFL), an elite professional football competition, elite junior Australian Football (AF) players need to develop certain physiological and anthropometric characteristics including jump height, running endurance, acceleration, and speed.1 Further, players need to be able to win contested possessions and frequently deliver the ball inside the attacking 50-m zone in order to score for their team.2 High training loads are required in order to develop these characteristics and help bridge the gap between elite junior and elite senior (AFL) competitions.3